Pain management in cervical cancer - Aguiar-Rosas, Sebastián; Plancarte-Sanchez, Ricardo; Hernandez-Porras, B. Carolina; García-Andreu, Jorge; Lezcano-Velazquez, Brenda Olivia; Reyes-Torres, Ignacio; Alarcón-Barrios, Silvia (Frontiers in Oncology, 2024)
Cervical cancer (CC) occupies the second place in incidence and mortality among women in México. Despite this, Cervical Cancer continues to have a late diagnosis which leads to a high rate of complications. Pain represents the most feared and disabling symptom, being present in up to 86% of patients with advanced disease. The approach to managing pain in this population has not been studied and described to a full extent. In addition, there is a pressing need to provide concise recommendations to promote adequate pain control. We performed a review of the literature in CC and had experts in the field of pain management evaluate the evidence found. We then issued relevant recommendations on pharmacology and interventional pain management. Thus, the approach to pain management must be comprehensive and individualized, considering the timely and appropriate use of pharmacologic treatment as well as interventional procedures.